Country water quality profiles: towards developing an African Water Quality Program (AWaQ) - Mukuyu, Patience; Jayathilake, Nilanthi; Tijani, M.; Nikiema, Josiane; Dickens, Chris; Mateo-Sagasta, Javier; Chapman, D. V.; Warner, S. (International Water Management Institute, 2024)
The African Ministers’ Council on Water (AMCOW) Secretariat committed to design and implement an African Water Quality Program (AWaQ) in its Strategic Operational Plan (2020-2024) considering the guiding frameworks it uses such as the Africa Water Vision 2025, United Nations Sustainable Development Goals (SDGs), and the African Union Agenda 2063: The Africa We Want. AMCOW reached out to the International Water Management Institute (IWMI) to support the development of such a program.